Learner Autonomy in English Language Learning: Vietnamese EFL Learners’ Perceptions and Practices - Tuan, Duong Minh (Universitas Pendidikan Indonesia, 2021)
Learner autonomy has been regarded as an important value which is expected to be present in any English language students as it can have positive effects on their learning. In Vietnam, the notion of learner autonomy has attracted more attention, and various studies have been conducted on teacher beliefs and practices regarding learner autonomy over the last decade. Nevertheless, not much evidence has been provided on how EFL students perceive and practise autonomous learning, especially at a time when there has been a shift towards student-centered instruction. To contribute to bridging this gap, this study is aimed to report on an investigation into Vietnamese EFL students’ perceptions and practices of autonomous learning. Data were collected from 50 English-majored students at a university in the Mekong Delta of Vietnam by using a questionnaire and a semi-structured interview. It was found that the students had an agreement on the importance of learner autonomy in their language learning. However, their perceived level of abilities to act autonomously was just above average. This result was the same as that found on their frequency scale of reported practices of autonomous activities inside and outside the classroom. Therefore, it is suggested that, to better enhance learner autonomy in teaching and learning English in Vietnam, it should be integrated into English language instruction by making it an integral part of EFL curricula.